Pelatihan Pengelolaan Lingkungan untuk meningkatkan Indeks Kualitas Lingkungan Hidup Kota Samarinda pada Kecamatan Samarinda Utara - Fahrizal Adnan,; Febrina Zulya,; Munaji Mahbub Afif, (ReTII, 2023)
Training of environmental management was conducted at district of North Samarinda. This program aimed to improve knowledge and commitment of all stakeholders in North Samarinda particularly about environmental management. This event, involving district, subdicstrict, RT , business owners, NGO, dan Mulawarman University. It contained lecture and discussion, and then signing of commitment letter about environmental management. All respondents showed improving knowledge and commitment.